2011
DOI: 10.1002/bio.1281
|View full text |Cite
|
Sign up to set email alerts
|

Determination of puerarin in biological samples and its application to a pharmacokinetic study by flow‐injection chemiluminescence

Abstract: A simple and sensitive flow injection-chemiluminescence (FI-CL) method has been developed for the determination of puerarin, based on the fact that puerarin can greatly inhibit CL of the luminol-H₂O₂-haemoglobin system. The inhibition of CL intensity was linear to the logarithm of the concentration of puerarin in the range 0.08-10.0 μg/mL (r²  = 0.9912). The limit of detection was 0.05 μg/mL (3σ) and the relative standard deviation (RSD) for 1.0 μg/mL (n = 11) of puerarin solution was 1.4%. Coupled with solid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Results were summarized in Table 3 as well as the results obtained by using hydrophilic interaction chromatography. It was found that there was no significant difference between the results obtained by the two methods (23,24).…”
Section: Sample Analysismentioning
confidence: 85%
“…Results were summarized in Table 3 as well as the results obtained by using hydrophilic interaction chromatography. It was found that there was no significant difference between the results obtained by the two methods (23,24).…”
Section: Sample Analysismentioning
confidence: 85%
“…Species specificity was found in pharmacokinetics of puerarin. The pharmacokinetics of puerarin in plasma of rats and dogs coincides with the two-compartment open model (Jin & Zhu, 1992; Yang et al., 2011; Ouyang et al., 2012), while in rabbits was best fitted to the three-compartment open model (Jin & Zhu, 1992).…”
Section: Pharmacokinetics Of Puerarinmentioning
confidence: 68%
“…Plasma samples were obtained from the Red Cross Blood Centre in Henan Province (China). Three different known amounts of standard solution of 2ME (5.0 × 10 ‐4 mol/L) were added to 200 μL serum samples, and then treated with triple methanol and thoroughly vortex mixed for 3 min . After centrifugation at 12,000 rpm for 15 min at 4°C, the supernatants were collected and diluted with water so that the final concentration of the drug was within the linear range of determination.…”
Section: Resultsmentioning
confidence: 99%